A new adenovector system for implementing thymulin gene therapy for inflammatory disorders. (July 2017) - Zappa-Villar, María F.; López-León, Micaela; Pardo, Joaquín; Costa, Mariana; Crespo, Rosana; Dardenne, Mireille; Goya, Rodolfo G.; Reggiani, Paula C.
Highlights: Thymulin is an anti-inflammatory peptide effective in brain and lung diseases. We constructed a regulatable adenovector expressing the genes for thymulin and GFP. This regulatable vector allows turning thymulin expression on and off as needed. It may be suitable for treating acute and chronic inflammatory diseases. Abstract: Thymulin is a thymic peptide possessing anti-inflammatory effects. In order to manipulate thymulin expression in gene therapy studies, we built a bidirectional regulatable two-vector Tet-Off system and the corresponding control system. The experimental two-vector system, ETV, consists of a recombinant adenovector (RAd) harboring an expression cassette centered on a Tet-Off bidirectional promoter flanked by a synthetic gene for thymulin and the gene for humanized Green Fluorescent Protein (hGFP). The second adenovector of this system, RAd-tTA, constitutively expresses the regulatory protein tTA. When cells are co-transduced by the two adenovector components, tTA activates the bidirectional promoter and both transgenes are expressed. In the presence of the antibiotic doxycycline (DOX) transgene expression is deactivated. The control two-vector system, termed CTV, is similar to ETV but only expresses hGFP. In CHO-K1, BHK, and C2C12 cells, ETV and CTV induced a dose-dependent hGFP expression. In CHO-K1 cells, transgene expression was almost completely inhibited by DOX (1 mg/ml). After intracerebroventricular injection of ETV in rats, thymulin levels increased significantly in the cerebrospinal fluid and there was high hGFP expression in the ependymal cell layer. When injected intramuscularly the ETV system induced a progressive increase in serum thymulin levels, which were inhibited when DOX was added to the drinking water. We conclude that our regulatable two-adenovector system is an effective molecular tool for implementing short and long-term anti-inflammatory thymulin gene therapy in animal models of acute or chronic inflammation.